2012
DOI: 10.1128/iai.06371-11
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Infection Enhances Apoptosis In Vivo through a Caspase-3-Dependent Mechanism in Experimental Periodontitis

Abstract: ABSTRACTThe purpose of this study was to test the hypothesis that diabetes aggravates periodontal destruction induced byAggregatibacter actinomycetemcomitansinfection. Thirty-eight diabetic and 33 normal rats were inoculated withA. actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 43 publications
(53 reference statements)
5
51
0
Order By: Relevance
“…Moreover, normal Wistar rats exhibited no alveolar bone loss induced by oral A. actinomycetemcomitans infection (46). In short, bone loss does not occur or develops slowly in wild-type rodents infected with human periodontal pathogens.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, normal Wistar rats exhibited no alveolar bone loss induced by oral A. actinomycetemcomitans infection (46). In short, bone loss does not occur or develops slowly in wild-type rodents infected with human periodontal pathogens.…”
Section: Discussionmentioning
confidence: 90%
“…This explains the greater alveolar bone loss in diabetic NOD mice compared with prediabetic and non-diabetic NOD mice [41]. It has been reported that A. actinomycetemcomitans infection accelerates alveolar bone loss in diabetic GK rats by increased rates of cell apoptosis in gingival epithelial and connective tissues [42,43].…”
Section: Discussionmentioning
confidence: 86%
“…For example, the concentration of caspase 3 in gingival crevicular fluid and serum has been seen to proportionally increase with the progression of periodontal disease (Abuhussein et al, 2014;Pradeep et al, 2014). Moreover, Aggregatibacter actinomycetemcomitans infection enhances apoptosis of osteoblastic cells, reducing osseous coupling through a caspase 3-dependent mechanism (Kang et al, 2012;Pacios et al, 2013). Caspase 3 is also involved in the Porphyromonas gingivalis-derived lipopolysaccharide-mediated activation of the MAPK signaling pathway in human periodontal ligament fibroblasts (Seo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have elucidated the relationship between caspases and periodontitis. For instance, Aggregatibacter actinomycetemcomitans infection enhances apoptosis through a caspase 3-dependent mechanism (Kang et al, 2012). Furthermore, caspase 3 expression increases with progression of gingival inflammation, probing depth, and clinical attachment level in periodontitis (Pradeep et al, 2014), and tissue destruction by Porphyromonas gingivalis involves both caspase 1-dependent and -independent mechanisms (Taxman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%